The Writer's Journey mythic structure for writers - Vogler, Christopher, 1949- (Studio City, CA : Michael Wiese Productions, 2007)
Vogler explores the powerfull relationship between mythomogy and storytelling in this clear, concise style that's made this book required reading for movie, executives, screenwriters, playwrights, fiction and non-fiction writers, scholars, and fans of pop culture all over the world.
filmography p. 371, bibliography p. 373, subject index p. 374
Includes bibliographical references (p. 373) and index.
Keywords: Motion picture authorship; Narration (Rhetoric); Myth in literature; Creative writing